Common features of spontaneity and stream of consciousness in prose, poetry and song lyrics - Yanush, Oleg (Current issues of Ukrainian linguistics: theory and practice, 2025)
The article deals with basic techniques and means of expression in literature like spontaneity and stream of consciousness. Taking into consideration different literary devices of expressing and depicting thoughts, experiences, moods, the author focuses on those two phenomena in language of prose, poetry, music lyrics of well-known authors of the 20th century. The author has deeply studied different researches on the topic, fulfilled particularly by prominent philosophers and psychologists of 19th and 20th centuries. Spontaneity is defined as human quality, which determines as well as influences the reaction on changing of certainty or unusual lifetime conditions. Within this connection the author mentions the theory for researching concepts of spontaneity and creativity. Attention is paid to spontaneity and creativity as different categories, but strategically linked. After all, he claims that a high degree of spontaneity does not mean creativity. Both categories can be applied in literature or song writing, in a skillful manner in particular. The author proposes the definition of the phenomenon of stream of consciousness as a stylistic device for the linguistic organization of the written text, which shows the complicated process of mental thinking with deep concentration on thoughts and feelings. Also, it is necessary to add that some authors determine several parts of this process (the stream): the pre-impulse to think, the thought, and the external circumstances at present time, that is simultaneously, evoking some reactions and changing the thinking process, closely connecting it with the concept of spontaneous poetry and prose. The attention has been emphasized on the spiritual life of the individual, the spontaneity of the emergence of thoughts and images, combination of the conscious and the unconscious, the rational and the sensual, increased emotionality, etc. Special attention is also paid to spontaneity and stream of consciousness as essential concepts in order to differentiate synonymic of lexemes denoting behavioral traits of a person’s character, which look alike at first glance only: impulsivity, improvisation and quick burst of emotionality. These characteristics of human actions have also been distinguished and differentiated. As a result of analysis of both concepts, the author concludes to support the idea of common features for spontaneity and stream of consciousness, taking into account that in literature these concepts are implemented in poetic texts as literary devices. That is why the necessity to explore literary works in further scientific investigations is signified by the represented research.